National Police and Civil Guard in TikTok: Comparison of the Two Accounts - Puebla-Martínez, Belén; López-Marcos, Casandra; Hidalgo-Cobo, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study analyses the use of TikTok as a communication tool by the Spanish security forces and corps. The main objective is to compare the use made by the Civil Guard and the National Police of this social network by considering the text that accompanies the videos published. A descriptive research with a quantitative approach through content analysis is carried out for this purpose. Regarding the communication strategy on TikTok, the results indicate that the National Police primarily focuses on security and crime-related aspects, while the Civil Guard showcases their daily work.